Zero-energy modes in serially coupled double quantum dots*Project supported by the National Natural Science Foundation of China (Grant Nos. 11774418 and 11374363). (June 2020) - Sun 孙, Fu-Li 复莉; Li 李, Zhen-Hua 振华; Wei 魏, Jian-Hua 建华
Abstract : We investigate symmetrically coupled double quantum dots via the hierarchical equations of motion method and propose a novel zero-energy mode (ZEM) at a temperature above the spin singlet–triplet transition temperature. Owing to the resonance of electron quasi-particle and hole quasi-particle, ZEM has a peak at ω = 0 in the spectral density function. We further examine the effect of the magnetic field on the ZEM, where an entanglement of spin and charge has been determined; therefore, the magnetic field can split the ZEM in the spectra.